Winter ecology of bighorn sheep in Yellowstone National Park - Oldemeyer, John Lee, author (Colorado State University. Libraries, 1966)
A bighorn sheep study was conducted on the northern winter range of Yellowstone National Park, Wyoming from June 1965 to June 1966. The objectives of the study were to census the bighorn population, map the winter bighorn distribution, determine plant composition and utilization on important bighorn winter ranges, observe daily feeding habits, and assess the effect of competition on bighorn sheep. Two hundred twenty nine bighorn sheep wintered on the northern winter range. These herds were located on Mt. Everts, along the Yellowstone River, on Specimen Ridge, and along Soda Butte Creek. The ewe to ram ratio was 100:78, the ewe to lamb ratio was 100:47, and the ewe to yearling ratio was 100:20. Range analysis was done on MacMinn Bench, Specimen Ridge, and Druid Peak. Range condition was best on Specimen Ridge and poorest on Druid Peak. Grass utilization varied from 50 per cent on MacMinn Bench to over 80 per cent on one key area on Druid Peak. Browse utilization was over 60 per cent throughout the winter range. Grasses made up 61.4, forbs 17.2, and shrubs 21.5 per cent of the bighorn's diet. The most important forage plants were bluebunch wheatgrass (Agropyron spicatum), Idaho fescue (Festuca idahoensis), phlox (Phlox sp.), Douglas rabbitbrush (Chrysothamnus viscidiflorus), and winterfat (Eurotia lanata). Competition between elk and bighorn sheep was mild during the study. Because of lighter than normal snowfall, elk were not forced to occupy bighorn winter ranges. Competition with elk was greatest on Specimen Ridge, where over 200 elk spent most of the winter.
Keywords: Mountain sheep; Animal ecology